MOLINA, HEBE BEATRIZ. 2011. Como crecen los hongos: La novela argentina entre 1838-1872. Buenos Aires: Teseo. - Sánchez, María Carolina (2012)
Fil: Sánchez, María Carolina. Universidad Nacional de Tucumán